PCR-SSCP typing of MHC in cattle and buffaloes - PIPALIA, D L; JOSHI, C G; RANK, D N; BRABMKSHTRI, B P; SOLANKI, J V (The Indian Journal of Animal Sciences, 2014)
BoLA-DRB3 gene polymorphism was investigated in 2 cattle breeds (Gir and Kankrej) and 2 buffalo breeds (Jaffrabadi and Mehsani) by PCR single strand conformation, Genomic DNA was isolated from 42, 45, 42 and 25 blood samples collected each from Gir, Kankrej, Jaffrabadi and Mehsani animals respectively, A 284 bp BoLA-DRB3 exon 2 segment was amplified by hemi-nesting PCR, using the locus specific primers, The PCR products were subjected to a non-denaturing gel electrophoresis on MDE gel. Out of total 16 SSCP patterns observed, Gir showed 13, Kankrej 10, Jaffrabadi 14 and Mehsani 4 different patterns.